Transmission of pressure head through the zone of tension saturation in the Lisseeffect phenomenon - Waswa, George W; Lorentz, Simon A. (Taylor & Francis, 2016)
The problem of transmission of pressure head through the zone of tension saturation in the Lisse effect(LE), i.e., the rapid response of groundwater level to pressurized pore air in the unsaturated zone, is investigated theoretically and experimentally. From the law of conservation of energy and the continuity equation, a one-dimensional diffusion equation is derived for transmission of pressure head through the zone of tension saturation. The solution to the equation is the pressure head at any point below the upper boundary of the zone of tension saturation and at any time after the compressed pore air pressure is imposed on the boundary. The key parameter, which determines the behaviour of transmis-sion of pressure head, is the newly proposed pressure head diffusivity coefficient. The theoretical results agree with the experimental results, obtained from laboratory column experiments in three physically different soils.
Keywords: compressed pore airpressure; diffusion equation; mathematical model; potential energy; rapid watertable response